Contextuality from Quantum Physics to Psychology - Dzhafarov, Ehtibar ... [et al.]. (Singapore : World Scientific, 2016)
"The book explores the variety of meanings of contextuality across different disciplines, with the emphasis on quantum physics and on psychology."--
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web. System requirements: Adobe Acrobat Reader.
Keywords: Quantum theory; Contextualism (Philosophy); Context effects (Psychology); Electronic books